Brief Communication: Climate, topographical and meteorological investigation of the 16-17 June 2013 Kedarnath (India) disaster causes - Singh, Rajesh; Siingh, Devendraa; Gokani, Sneha A.; Buchunde, P.S.; Singh, R.P.; Singh, A.K. (My University, 2015)
The devastating episode (17–18 June 2013) at Kedarnath (Uttrakhand, India) caused huge loss of lives and physical/material wealth. To understand this catastrophic event, rainfall/convective data and associated climate meteorological parameters are investigated. Low pressure zone with very high cloud cover (60–90%), and relative humidity (70–100%) associated with low (< 4 m s−1) wind velocity over Kedarnath region during 15–17 June are observed. The cause of disaster seems to be the heavy and continuous rainfall associated with snow melting and over flooding/collapse of the Chorabari Lake, located upstream. Monsoon advancement was much faster due to the presence of convectively active phase of the Madden Julian Oscillation.
Keywords: Climate; Topographical; Meteorological; Disaster causes; Kedarnath; Monsoon